Nature-Integrated Day-Care Spaces: Fostering Early Childhood Growth in Lucknow - Aiman Raza; Pooja Singh; Samreen S. Siddiqui; Deepti P. Rana (International Journal of Architectural Design and Planning, 2026)
The physical environment plays a vital role in shaping early childhood experiences, influencing cognitive, emotional, and social development. However, in rapidly urbanizing cities such as Lucknow, children’s exposure to natural environments has become increasingly limited, with most day-care centers confined within enclosed, concrete settings. This study investigates how the integration of natural elements within day-care interiors and outdoor spaces can foster holistic child development and enhance learning outcomes. Emphasizing the principles of biophilic and child-centered design, the research examines how elements such as natural lighting, ventilation, greenery, open play areas, and sensory interaction zones contribute to children’s well-being, creativity, and concentration. Employing a qualitative and case study-based methodology, the research involves spatial assessments of selected day-care centers, behavioral observations of children’s activities, and structured interviews with parents, teachers, and caregivers. The findings are expected to reveal a strong correlation between nature-integrated spatial design and improvements in children’s cognitive engagement, emotional balance, and social interaction. The study further aims to develop a set of design and policy guidelines for sustainable, nature-based child-care environments suited to the urban context of Lucknow. By reimagining day-care spaces as nurturing environments that harmonize nature and built form, this research highlights the potential of design as an active agent in promoting early childhood growth, environmental awareness, and overall well-being
Keywords: Biophilic Design; day-care architecture and interiors; early childhood development; nature-integrated spaces; urban sustainability